THE IMPACT OF PLUG-IN HYBRID VEHICLES IN LOW-VOLTAGE DISTRIBUTION SYSTEMS USING A MONTE CARLO SIMULATION - Smilkoska, Evica; Zdraveski, Vasko; Vuletić, Jovica; Angelov, Jordančo; Todorovski, Mirko (Journal of Energy Technology, 2025)
The growing presence and randomness of renewable-based Distributed Generation, such as solar, photovoltaic, and wind power, and heavy Plug-in Hybrid Electric Vehicle loads in residential distribution grids result in both a higher degree of imbalance and a wide range of voltage fluctuations. When increasing the number of Plug-in Hybrid Electric Vehicles that are simultaneously charged, the additional unpredicted load may cause several problems to the current grid in terms of voltage deviations, thermal overloads, power losses, increased aging of transformers and lines, decreased quality of supply, and power outages. This paper proposes an approach that models Plug-in Hybrid Electric Vehicles’ behaviour and performs power flow analysis on CIGRE low voltage benchmark grid to investigate the impact on the current distribution grid.